Status of Scheduled Caste Women Entrepreneurs in Kerala - Saritha A K (RESEARCH REVIEW International Journal of Multidisciplinary, 2019)
Scheduled castes facing employment discrimination operates through traditional mechanisms, social hierarchy and culture. Less participation in employment not arise the issue of equal payment to male and female. Oppressed and politically marginalised group Dalits or Scheduled Castes have the periodical service of untouchable works like digging village graves, disposing dead animals, street cleaning and promoting to leather work, cobblers, agricultural work and manual scavengers etc. there is no wage no income in service. Intrinsically, wanting social development is high, getting education, employment, income, health, wealth etc. need to demanding. With the help of government and reservation system, entrepreneurship definitely improves the confidence level to live like others by adding social network. Through SC women entrepreneurship assist their community development beyond women empowerment.